2002
DOI: 10.1046/j.1537-2995.2002.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of HIV in blood

Abstract: These results suggest that PEN110 inactivates HIV-1 by targeting the viral nucleic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Most inactivation approaches use chemicals that bind nucleic acids either directly (40) or when subjected to UV light (16), preventing viral replication. The toxicity and mutagenicity of these chemicals raise significant concern.…”
Section: Discussionmentioning
confidence: 99%
“…Most inactivation approaches use chemicals that bind nucleic acids either directly (40) or when subjected to UV light (16), preventing viral replication. The toxicity and mutagenicity of these chemicals raise significant concern.…”
Section: Discussionmentioning
confidence: 99%
“…To broaden the spectrum of pathogens inactivated by PEN110, Laso and colleagues extended the 22 ± 2°C incubation period to 22 ± 2 h [41]. Under these conditions, ≥ 5·5 log 10 of Sindbis virus, ≥ 6·3 log 10 of VSV, ≥ 6·4 log 10 of BVDV, ≥ 6·5 log 10 of PRV, ≥ 6·0 log 10 of PPV, ≥ 6·5 log 10 of reovirus 3, ≥ 4·7 log 10 of Adenovirus‐2, ≥ 6·6 log 10 of vesicular exanthema of swine virus, ≥ 6·7 log 10 of foot and mouth disease virus, ≥ 6·7 log 10 of bluetongue virus, ≥ 7 log 10 of WNV, ≥ 5 log 10 DHBV, as well as ≥ 5·57 log 10 of extracellular HIV‐1 and ≥ 4·5 log 10 of cell‐associated HIV were inactivated [41–44]. Other studies demonstrated complete prevention of the outgrowth of 10–100 CFU/ml of Yersinia enterocolitica , Pseudomonas fluorescens and Pseudomonas putida during 42 ‐day storage of RBCs treated with 0·1% PEN110 for 24 h [45] and inactivation of ≥ 5·6 log10 of Acinetobacter lwoffii , ≥ 6·1 log 10 Acinetobacter johnsonii , ≥ 4 log 10 of Clostridium perfringens and ≥ 5 log 10 of Proprionibacterium acnes [46].…”
Section: Akylating Agentsmentioning
confidence: 99%
“…[85][86][87] The INACTINEs are stable monoalkylators that are immediately active upon addition to blood or red cell concentrates (Fig. INACTINE (PEN 110), a nucleic acid-targeted compound, was reported to inactivate viruses, bacteria, and leukocytes in red cell suspensions.…”
Section: Potential Systems For Inactivation Of Pathogens In Red Cell mentioning
confidence: 99%